“MAMA” mobile application for pregnancy knowledge and anxiety: A quasi-experimental study - Ningsih, Dini Cristia; Widyawati, Widyawati; Lismidiati, Wiwin (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2025)
Introduction: Pregnancy is a critical phase in a woman’s life that induces a range of alterations, including physical, emotional, and social changes. Prenatal anxiety, often known as anxiety during pregnancy, is a prevalent psychological illness that frequently manifests throughout the gestation period. Knowledge is an indicator of anxiety levels throughout pregnancy. The objective of this study was to assess the impact of implementing the MAMA mobile application intervention on the level of awareness and anxiety related to pregnancy among pregnant women. Methods: This study employed a quasi-experimental design, which included a pretest and posttest, along with a control group that was not equivalent to the experimental group. This study followed a quantitative method and was conducted at two community health centres in the Sleman, Yogyakarta area for the control group and intervention group. We conducted the research from December 2019 to March 2020. The participants in this study were exclusively third-semester pregnant women who received care at community health centres and matched the specified research requirements. The sample size for each group consisted of 39 respondents. This study included a knowledge questionnaire to assess pregnancy knowledge and the HRSA questionnaire to assess pregnancy anxiety.Results: The research results indicate a significant impact on the knowledge variable in the intervention group before and after they received the MAMA mobile application (p=0.000). In addition, the intervention group experienced an influence on the anxiety variable before and after receiving the MAMA mobile application (p=0.018). Conclusion: The mean difference test comparing the control group to the MAMA mobile application group revealed a significant impact of the application on pregnant knowledge. However, we observed no significant effect on pregnancy anxiety.